PATIENT SATISFACTION AND ITS RELATIONSHIP WITH THE QUALITY OF COMPREHENSIVE EMERGENCY OBSTETRIC AND NEONATAL CARE (CEmONC) IN THE GENERAL HOSPITAL OF PANEMBAHAN SENOPATI BANTUL - Fitri Dian Kurniati; Lely Lusmilasari; Sri Mulatsih (Belitung Raya Foundation, Indonesia, 2017)
Background: Patient satisfaction has emerged as an increasingly important health outcome and is currently used to evaluate the quality of care. Objective: To describe the level of satisfaction of mothers after caesarean section and examine its relationship with the quality of Comprehensive Emergency Obstetric and Neonatal Care (CEmONC). Methods: This was an analytic descriptive study using cross-sectional design. The study was conducted in Alamanda ward in the General Hospital (RSUD) of Panembahan Senopati Bantul Indonesia during September until November 2016. There were 55 respondents selected using purposive sampling. The instruments included The Scale for Measuring Maternal Satisfaction (SMMS) – caesarean birth and the Quality of CEmONC questionnaires. Spearman’s rho and logistic regression were performed for data analysis. Result: Results showed that 47.3% respondents rated the quality of CEmONC in high category and 56.4% were satisfied. The correlation value between quality of CEmONC and patient satisfaction was 0.285 (p = 0.035; OR = 1.96). Conclusion: Level of satisfaction of mothers after caesarean section was associated with the quality of CEmONC in the General Hospital of Panembahan Senopati Bantul Indonesia.